The Effect of Motion Graphic Animation Videos on the Level of Final Exam Anxiety of Grade XII Students at MAN 3 Cijantung - Erma Amelia Rahayu; Peni Cahyati; Ridwan Kustiawan; Dudi Hartono (Faculty of Medicine, Universitas Tadulako, 2026)
Background: A negative emotional response to real or imagined threats accompanied by personal experiences such as stress, fear, and feelings of uneasiness is called anxiety. Adolescents aged ten to twelve most often experience anxiety disorders. Objectives: The purpose of this study was to determine how motion graphic animation videos affect students' anxiety levels before the final exam of class XII at MAN 3 Cijantung. Methods: This research method is quasi-experiment with pre-test post-test with control design and non-probability sampling technique with 36 students in class XII. Results: The results of the study in the intervention group and control group experienced significant changes in the mean score and anxiety level. In the intervention group before treatment was 37.89 and decreased to 22.17 with a minimum score of 12 or no anxiety (p-value 0.001). In the control group, the mean score was 31.21 to 29.06 with a minimum score of 19 (p-value 0.047). Conclusions: The conclusion of this study is the p-value analysis test of 0.007 (p-value <0.05) which shows that the provision of animated videos is more effective in overcoming anxiety disorders. Distraction using this animated video can be used as an alternative way that can be used to overcome anxiety.